Implementation of the Scrum Method in a Senior High School Academic Information System - Fajar Agustini; Euis Widanengsih (INFOKUM, 2026)
Delays in system completion, continuously evolving requirements, and ineffective communication between developers and users are common challenges in information system development. This study aims to implement the Scrum method in the development of an Academic Information System for Senior High Schools (SMA) to address these issues. Scrum was selected as an agile software development framework that emphasizes iterative, adaptive, and collaborative processes. The research methodology employed is Action Research, in which system development is conducted through multiple sprints, each consisting of planning, execution, review, and retrospective phases. The implementation results indicate that the Scrum method successfully increased development progress transparency by 40% and reduced feature deviation from user requirements (scope creep) by 30%. In addition, the developed system was completed 25% faster than the estimated timeline using the waterfall method. The resulting system has been integrated with core academic modules, including student admission (PPDB), scheduling, grade processing, and reporting. This study concludes that Scrum is not only effective in accommodating dynamic requirement changes but also enhances stakeholder satisfaction—particularly among school administrators and staff—through their continuous involvement in sprint review activities. Overall, the implementation of Scrum proves to be a viable solution for information system development in educational institutions.